Mixed infected laryngocoele presenting as airway obstruction: a case report. Issue 2 (28th February 2021) - James, Danielle L; Garry, Stephen; Corbett, Mel; Lang, John
Abstract: Laryngocoele is a rare entity, defined as an abnormal cystic dilatation of saccule of the laryngeal ventricle. Three types of laryngocele have been described, based on their relation to the thyrohyoid membrane: internal, external or mixed type. Symptoms are variable, including neck swelling, shortness of breath, dysphonia and fever, if the laryngocoele becomes infected. Patients may also present in extremis with airway obstruction. We present the case of a healthy 34-year-old gentleman with acute airway obstruction due to a mixed infected laryngocoele. Flexible nasoendoscopy showed a large cystic swelling arising from the laryngeal ventricle. Computed tomography of neck confirmed a right paraglottic collection extending into the ventricle and glottis, causing significant airway compromise. The patient was managed with microlaryngoscopy and cystic decompression. At outpatient follow up, he was completely asymptomatic and is currently under surveillance. Endoscopic decompression is a safe and effective initial management for mixed laryngocoele.